A technique to determine priority areas of cooperation between the units of the Interior Troops of the Interior Ministry of Ukraine and the formations of civil defense forces of the Ministry of Emergencies and Affairs of Population Protection from the Con - Poberezhnyi, А. А.; Neklonsky, І. М. (Honor and Law, 2019)
A technique to determine priority areas of cooperation between the units of the Interior Troops of the Interior Ministry of Ukraine and the formations of civil defense forces of the Ministry of Emergencies and Affairs of Population Protection from the Consequences of Chornobyl Catastrophe of Ukraine in emergency situations is given. An appropriate software to ensure the systematization of the expert evaluation results and the choice of the most efficient coordination mechanism are described.